Balloon pulmonary angioplasty improves quality of life in Japanese patients with chronic thromboembolic pulmonary hypertension. Issue 2 (August 2020) - Minatsuki, Shun; Kodera, Satoshi; Kiyosue, Arihiro; Saito, Akihito; Maki, Hisataka; Hatano, Masaru; Takimoto, Eiki; Komuro, Issei
Highlights: Balloon pulmonary angioplasty (BPA) improved the European Quality of Life Five Dimension (EQ-5D) index mainly by improving daily activities. Mean pulmonary artery pressure is achieved below 25 mmHg through BPA to improve their prognosis. In some patients, impaired quality of life remains after BPA, which can be quantified by EQ-5D. The improvement was significantly correlated with hemodynamic status and 6-minute walking distance. Abstract: Background: The conventional treatment goal for chronic thromboembolic pulmonary hypertension (CTEPH) is improving hemodynamic status, particularly mean pulmonary artery pressure (mPAP); however, some patients complain of impaired quality of life (QOL) caused by dyspnea on effort, even after hemodynamic status has fully improved. It remains unclear whether treatment for CTEPH can improve patients' QOL or whether quantitative measures of QOL correlate with hemodynamic status. This study quantified QOL among Japanese CTEPH patients and investigated whether balloon pulmonary angioplasty (BPA) improved QOL. Methods and results: We calculated the QOL scores of 45 CTEPH patients using the European Quality of Life Five Dimension scale (EQ-5D). The mean QOL score among 12 of those 45 not involved in any therapy except supplemental oxygen at the time of initial measurement was 0.673 ± 0.251. QOL was measured before and after BPA for 17 patients, and the mean significantly improved (QOL from 0.741 ± 0.195 to 0.802 ± 0.160, p  < 0.05; mPAP from 33.0 ± 8.4 to 23.4 ± 4.2 mmHg, p  < 0.05; pulmonary vascular resistance from 441.4 ±  214.2 to 268.4 ± 85.6 dyne/s/cm 5, p  < 0.05). Moreover, the index significantly correlated with mPAP ( r  = −0.37, p  < 0.05), pulmonary vascular resistance ( r  = −0.40, p  < 0.05), 6-min walking distance ( r  = 0.45, p  < 0.05), and percutaneous oxygen saturation at rest ( r  = 0.32, p  < 0.05). Regarding individual items, median values improved only regarding "usual activities." Our findings prove that BPA improved QOL measured by the EQ-5D in Japanese CTEPH patients by improving "usual activities" scores. Conclusion: BPA improved QOL in patients with CTEPH mainly by improving "usual activities, " besides the improvement in mPAP.